Answer:
x = 2 y = 5
Explanation:
Since we know that
x = y - 3
We can insert that into the equation above:
2(y-3) + y = 9
After having this equation, we can start by multiplying the numbers/variables in the parenthesis by 2.
2y - 6 + y = 9
Then add the common multiples (2y and y)
That makes:
3y - 6 = 9
We need to get 3y on a side by itself, so to do this, we can add 6 to (-6) and (9)
That makes:
3y = 15
Divide the 3 by 3 and 15 to get the y on its own:
y = 5
Now we need to find x, and to do this we can insert y into the equation:
2x + 5 = 9
Now subtract the 5 from the (5) and (9) and you'll get
2x = 4
Then you divide the 2 on both sides and get
x = 2
You can check your work by inserting x and y into the equation
2(2) + 4 = 9
Sorry for this super long explanation, and hope this helps